Analisis Mikro-Longitudinal Berbasis Systemic Functional Grammar dalam Pemerolehan Semantik pada Anak Usia 4 Tahun - Nurhasanah; Ridha Hasnul Ulya; Suci Novira Putri; Sadira Argiyanti; Nabila Syafri Falencia; Salsabila Aprila Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the semantic acquisition trajectory of four-year-old children through observations of natural interactions. Using a micro-longitudinal mixed-methods design over one and a half months, spontaneous utterances were collected through a listening and conversation technique and validated through triangulation by linguistic experts. Quantitative analysis included the distribution of frequency categories and the calculation of Mean Length of Utterance (MLU), which was integrated qualitatively with the Systemic Functional Grammar framework. The results identified eleven semantic categories with a dominance of locative/spatial (20%), attributive (15%), and negation (15%). The MLU value of 3.65 morphemes confirmed the developmental transition from telegraphic structures to the formation of complex and relational clauses. Functionally, children's utterances actualized the metafunctions of all three languages ​​simultaneously, reflecting the differentiation of meanings bound by context and communicative purposes. It was concluded that semantic acquisition is a multidimensional process reflecting the synergy between cognitive, representational maturity, and socio-pragmatic adaptation. The implications of this research include the development of normative indicators for language assessment, contextual linguistic stimulation strategies, and the acquisition of an ecological interaction-based language acquisition model that is relevant to psycholinguistic development and early childhood education.